2023
DOI: 10.54393/pjhs.v4i02.465
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Findings of Ventriculomegaly in 2nd And 3rd Trimester with Fetal Outcomes

Abstract: In the second trimester, fetal ventriculomegaly is a typical finding on obstetrical ultrasonography. It is clinically relevant since it can be caused by a variety of disorders that cause brain, motor, and/or cognitive impairment. Many cases are associated with other abnormalities, but in other cases, ventriculomegaly is the only abnormality. Objective: To evaluate the incidence of ventriculomegaly in 2nd and 3rd trimester with fetal outcomes. Methods: A descriptive study was conducted at of University of Lahor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Zhao et al, studied the discovery of chromosomal abnormalities during prenatal ultrasonography in fetuses with isolated ventriculomegaly. They concluded that there was a high chance of chromosomal abnormalities in fetuses with solitary ventriculomegaly, particularly if it was severe, bilateral, rst present in mid-gestation, and did not go away [20]. Out of 774(100.0%) patients, 21(2.7%) patients had fetal spinal defects.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al, studied the discovery of chromosomal abnormalities during prenatal ultrasonography in fetuses with isolated ventriculomegaly. They concluded that there was a high chance of chromosomal abnormalities in fetuses with solitary ventriculomegaly, particularly if it was severe, bilateral, rst present in mid-gestation, and did not go away [20]. Out of 774(100.0%) patients, 21(2.7%) patients had fetal spinal defects.…”
Section: Discussionmentioning
confidence: 99%